POPULATION PREDICTION OF SIMALUNGUN DISTRICT USING THE LOGISTIC MODEL IN 2025-2030 - Dora Latersia P, Egya; Jehan Maulana, Putri; Nada Utami, Destia; Rizki Hanafi, Muhammad (Pena Cendekia Insani, 2024)
Population growth prediction is an important aspect in regional development planning, including in Simalungun Regency, which has complex demographic dynamics. Based on data from BPS, the population in Simalungun Regency is increasing every year, so a solution is needed to reduce the negative impact so that there is no population explosion. The solution that can be used to project the population in Simalungun Regency is to use a logistic growth model. This model is used to calculate the value of the growth rate and environmental carrying capacity (Carrying Capacity) using population data in Simalungun Regency in 2019-2023. The results obtained show that the environmental carrying capacity that limits the population in Simalungun Regency is 1,005,168.408 people. With the relative growth rate per year of the population in Simalungun Regency using the logistic model I is 3.46%. This model also projects the population in Simalungun Regency from 2025-2030. The population in 2025 amounted to 1,374,983 people until the year 2030 is estimated to amount to 1,476,292 people.